Tensões, uso e apropriação da terra no Xingu: o caso da RESEX “Verde para Sempre”, Porto de Moz/PA - GONÇALVES, Maria Raimunda Martins (Universidade Federal do Pará, 2012)
The peasants' struggle for land in the Xingu at the turn of the twentieth century is the focus of this work. We will deal with forms of organization and struggle of the peasantry within the global/local dynamic that led to the creation of the extractive reserve "Verde para Sempre" in the municipality of Porto de Moz, state of Pará. It was in memory of social groups and through the research field that we seek the peasant perspective of development, and its actions and strategies to remain in their territories against the advancing of big business to the field from the 1960s in the Amazon.